Between the Show and the War. Sports as a generator of emotions and architecture of sports venues - Lidin, Konstantin (project baikal, 2017)
The author proposes definition of sports as means of production of sthenic emotions concerning demonstration of human physical and psychic abilities, hic et nunc. The article tells how sports bear a close resemblance to such fields as military art and show business. Architecture of sports venues is viewed through history in connection with the changes in interrelations between these three fields.
Keywords: sports; architecture; philosophy; social psychology; psychology of emotions